Technical skills, knowledge competencies and expected changes in the clothing industry - Kamis, Arasinah; Bakar, Ab. Rahim; Hamzah, Ramlah; Asimiran, Soaib; Ab. Halim, Norhaily (BEST Journals, 2014)
Thus the purpose of this study is to determine the competency of technical skills, knowledge and expected changes in the apparel industry within the next 10 years. Interview results found that technical competency that is most preferred are drawing, designing, sewing techniques and computer skills. The study found that knowledge of the preferred competency is the latest trends, knowledge in fashion and knowledge of business strategy. Changes in the fashion in the next ten years is also expected to be influenced by the entertainment, popular culture from foreign countries, except patterns and shapes often look the same as the trend that has existed in the 1960s or 1970s. The findings provide plenty of space and ideas to the curriculum and teaching that can be used to streamline the fashion and apparel curriculum to produce graduates who obtained competencies in line with the needs of employers, apparel industry and as a guide to starting a business in the future.